A contribution to age determination of cheetahs (Acinonyx jubatus) based on radiographic analysis of the skull and postcranial morphology. - Schmidt, Martin J; Steenkamp, Gerhard; Failing, Klaus; Caldwell, Peter; Kirberger, Robert M; Justus Liebig University Giessen (My University, 2019)
The aim of this retrospective cross-sectional study was to present comprehensive information about the age-dependent change of skeletal characteristics in captive cheetahs with known age and to assess the benefit of these variables for age estimation in this species. Radiographs of 162 known-age captive and semi-captive cheetahs were retrospectively examined and age-related changes of skull, axial and appendicular skeletal systems were documented. Metric and non-metric variables were used. These parameters were checked for the best correlation with age using a multiple stepwise regression analysis. An overview about the time frames, in which ossification centers appeared and physeal closure occurred is presented. Multiple stepwise regression analysis revealed the status of closure of the coronal suture, the maximum length of the frontal sinus, the condylobasal-, hard palate, and facial length are most significantly correlated with age. Together with the pulp size of the upper canine, these values can be used for an age approximation in cheetahs.
Keywords: ddc:630